Comparison of mental health status of married and unmarried girls of late adolescent age in an urban slum of Delhi - Sujata Gupta; Neha Taneja; S K Kapoor; Amod Kumar (Wolters Kluwer Medknow Publications, 2020)
Introduction: Late adolescence age (16-19 years) is organized around central task of achieving an identity. In India, age at marriage for girls has been legally declared as 18 years, but many girls are married much before this age. Early marriage for girls can have profound psychological and emotional impacts. Aims and Objectives: The aim was to study the impact of marriage on mental health of married girls of late adolescent age and to compare them with unmarried girls of the same age. Materials and Methods: A comparison study was conducted among girls of late adolescent age in an urban slum of North East Delhi. Background information was collected through oral questionnaire method. The mental health of the study participants was assessed using validated tool "General Health Questionnaire-12" and "Symptom Checklist-90." Results: Education and economic status of participants and parents were significantly associated with early marriage. Majority of married girls were found to be associated with risk of developing mental health disorders.